Program Kerja di Community Learning Center (CLC) Cempaka, Kundasang, Sabah, Malaysia - Hanifah Harviatulhaq (LP2M Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2023)
The work program at Cempaka Community Learning Centre (CLC), Kundasang, Sabah, Malaysia, is designed to improve the quality of education with various learning activities. Through the Independent Overseas Collaborative KKN of UIN Sunan Gunung Djati 2023, several programs were implemented, including English language learning, national literacy, hand washing, and emotion check. Initial observations showed that students' interest in this learning was high. The program was conducted using the peer tutor method, and the results showed an increase in students' knowledge and skills in various aspects. The program is expected to continue and be adapted to specific needs in the future.